(untitled) (Світ фінансів, 2017)
Жуковська А. Ю. Концептуальна парадигма функціонування суспільно-добровільного сектора економіки в Україні. Розглянуто актуальні питання функціонування суспільно-добровільного сектора економіки. Проаналізовано вітчизняну нормативно-правову базу функціонування суспільно-добровільного сектора та запропоновано шляхи її удосконалення й адаптації до відповідних європейських стандартів. Zhukovska A. Conceptual paradigm of functioning of public-voluntarily sector of economy in Ukraine. The pressing questions of functioning of public-voluntarily sector of economy are examined. The domestic normatively legal base of functioning public sector is analyzed and ways on its improvement and adaptation to the proper European standards are offered.